Patterning and manipulating microparticles into a three-dimensional matrix using standing surface acoustic waves - Nguyen, Tan Dai (2019)
A method based on standing surface acoustic waves (SSAWs) is proposed to pattern and manipulate microparticles into a three-dimensional (3D) matrix inside a microchamber. An optical prism is used to observe the 3D alignment and patterning of the microparticles in the vertical and horizontal planes simultaneously. The acoustic radiation force effectively patterns the microparticles into lines of 3D space or crystal-lattice-like matrix patterns. A microparticle can be positioned precisely at a specified vertical location by balancing the forces of acoustic radiation, drag, buoyancy, and gravity acting on the microparticle. Experiments and finite-element numerical simulations both show that the acoustic radiation force increases gradually from the bottom of the chamber to the top, and microparticles can be moved up or down simply by adjusting the applied SSAW power. Our method has great potential for acoustofluidic applications, building the large-scale structures associated with biological objects and artificial neuron networks.